The Relationship Between Work Involvement and Organizational Climate with OCB in State Civil Apparatus at the Department of Health Limapuluh Kota Regency - Mona Gusfira; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin; Genius Umar (Pascasarjana, Universitas Negeri Padang, 2022)
The background of this research is from an initial survey conducted on Monday, December 19, 2016 at the Limapuluh Kota Regency Health Office, the results showed that there were employees who lacked Organizational Citizenship Behavior (OCB) behavior. This study aims to determine the relationship between OCB in the State Civil Apparatus (ASN) of the Limapuluh Kota Regency Health Office with work involvement and organizational climate. The research sample consisted of 93 civil servants at the Limapuluh Kota Regency Health Office, with the sampling technique calculated using the Yamane formula in Slovin. Multiple Regression Analysis is a data analysis method used in this study. The research results reveal that on the work involvement variable (X₁) with a significance level of 95% (α = 0.05) and a significant number (P-value ) of 0.000 <0.05, then H₀ is rejected or it means the work involvement variable (X₁) has a significant influence on OCB (Y). While the organizational climate variable (X₂) has a significant level of 95% ( α = 0.05) and a significant number (P-value ) of 0.004 <0.05, then H₀ is rejected or it means the organizational climate variable (X₂) has a significant influence on OCB (Y). And the results of the F-test were 42.067 with a significance figure (P-value) of 0.000, with a significance level of 95% (α = 0.05) and a significant figure (P-value) of 0.000 <0.05, then H₀ was rejected or it means variable work involvement (X₁), and organizational climate (X₂) has a significant influence simultaneously on OCB variables (Y). This study also shows that work involvement (X₁) and organizational climate (X₂) can explain the dependent variable OCB (Y) of 47.2%, while the remaining 52.8% is explained by other factors not examined.